Development of carbon nanotubes-reinforced polyamide 12 composite powders for 3D printing - Woon, Kun Kuan (2016)
Ever since the introduction of Additive Manufacturing (AM) technology to this rapidly growing world, researches and studies on its practicality have been carried out so as to make sure that this technology is being made full use of in the development of countries. Over the decades, AM techniques have been evolving and until today it is the Selective Laser Sintering (SLS) Technique that is predominantly used over other available techniques. At the same time, more and more materials with wide range of properties have been developed for SLS technique. One of the most widely used materials is Polyamide 12.